The Role of Heat Shock Proteins in Cisplatin Resistance - Krawczyk, Zdzisław; Gogler-Pigłowska, Agnieszka; Sojka, Damian R; Scieglinska, Dorota (Anti-cancer agents in medicinal chemistry, 2018)
Cisplatin (CDDP), a small molecule platinum-based compound, is an effective anticancer drug used against a wide range of human neoplasms. Long-term clinical use of CDDP is however limited due to the development of drug resistance and the possible incidence of serious side effects including nephrotoxicity and ototoxicity. The mechanisms underlying resistance of cells to CDDP are complex, and among them, the cytoprotective involvement of proteins referred to as Heat Shock Proteins (HSP) seems potentially important. We searched various electronic databases including PubMed and selected the reports concerning the contribution of HSPs to CDDP resistance of cancer cells and to minimize the CDDP-induced nephrotoxicity and ototoxicity. This critical review of data collected so far summarizes the results on the major HSPs: HSP27/HSPB1, HSP70/HSPA1, HSP90/HSPC and GRP78/HSPA5, because only these have been the subject of the most intense research in the matter discussed here. We also provide relevant information concerning some other HSPs, namely HSPA9/mortalin, HSPA2, HSP110 and DNAJ. A possible role of HSPs in counteracting CDDP-induced neprho- and ototoxicity is mentioned. This review shows that no universal relationship between the levels of expression of HSPs and sensitivity of cancer cells to CDDP can be confirmed. Multiple observations indicate however that such correlation can rather manifest as a molecular or cellular context-dependent phenomenon. Thus, HSPs can be viewed as an important component of the multifactorial, complex response of cancer cells to CDDP. However, to strengthen such a conviction, more extensive studies are needed.